ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CSR PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Chandra Kristiana, Rispantyo & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research was to analyze the influence of company size, profitability and leverage to the Corporate Social Responsibility disclosure. This research method using case studies on the company's industrial sector manufacturing consumer goods registered in BEI during period 2013-2014. This study uses secondary data annual report of the company. The sampling method in this study is purposive sampling. Total number of samples in this study were 68 research samples. The analysis technique use in this study is the method of multiple linear regression the results of this research indicated that the company size has a significant positive influence on the CSR Disclosure, while profitability and leverage has no influence on the CSR DisclosureKeywords: CSR disclosure, company size, profitability and leverage